Analysis of key challenges to implementation of FEFO in perishable food supply chain - Kandasamy, Jayakrishna; Vimal, K. E. K.; Singh, Aditya Pratap; Magnani, Aaryan; Gokhale, Ameya; Jagtap, Sandeep (Elsevier, 2025)
Implementing FEFO practices has become essential for organizations globally to minimize spoilage, enhance inventory turnover, and ensure compliance with health and safety standards. To aid stakeholders in effectively adopting FEFO, it is crucial to identify and address the challenges involved in its implementation. Through an extensive literature review using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) methodology and insights from industry experts, this study identifies thirteen core challenges that hinder FEFO adoption. PRISMA methodology was used to systematically organize the existing literature for the purpose of this study. Using tools like Decision Making Trial and Evaluation Laboratory (DEMATEL) and Total Interpretive Structural Modelling (TISM), the challenges were examined and ranked according to their interdependencies, providing insights into the cause-effect relationships among them. After applying DEMATEL, an alpha threshold value of 0.368 revealed that challenges in effective storage management are the primary barrier in implementing FEFO practices. With level partitioning, this challenge emerged as the most significant, forming the foundation for a roadmap designed to assist stakeholders. The findings from this study offer managers actionable insights for implementing effective FEFO techniques within their organizations. The study's novelty lies in its combination of DEMATEL and TISM methodologies, along with a roadmap that highlights strategic and policy-focused recommendations to support efficient FEFO adoption and the systematic study of challenges preventing effective FEFO adoption. This paper aids implementation of FEFO for better inventory control and management, reduced wastage and greater efficiency. The paper also effectively outlines and analyses the order of importance of challenges in FEFO implementation and their interdependence.
Keywords: First-in first-out; First expired first out; Inventory management systems; Perishable food supply chain; Total interpretive structural modelling; Decision-making trial and evaluation; laboratory; 46 Information and Computing Sciences; 4609 Information Systems; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 8.3 Policy, ethics, and research governance; Generic health relevance